Indiscriminate Use of Antibiotics in Neurotrauma Patients Referred for Expert Neurosurgical Care in a Developing Country - Oyemolade, Toyin A. (J Neurosci Rural Pract, 2019)
Background In Nigeria, pre-neurosurgical care of most neurotrauma patients usually involves administration of many empirical agents including antibiotics with no apparent indications. This practice is fraught with two particular dangers: increase in health care costs and development of drug resistance. This study aimed to interrogate antibiotic stewardship in the pre-neurosurgical care of neurotrauma patients referred to our practice. Materials and Methods This 7-month prospective descriptive study was performed in one University Teaching Hospital of a developing country. Clinical data on all admitted neurotrauma patients with information on the pre-neurosurgical treatment received were captured and analyzed. Results There were 113 patients, 87(77.0%) males; 103(91.2%) had head injury, and 10(8.8%) spinal cord injury. Associated systemic injuries occurred in 47(41.6%): 40 involved skeletal and soft tissue systems, and 12(10.6%) presented with aspiration pneumonitis. These patients were referrals from public health facilities including primary health facilities (PHF), secondary (SHF), and tertiary (THF), as well as private clinics (PC). Antibiotics were given to 74 (65.5%) patients, with a probabilistic indication in only 17.6% (13/74) of these. The proportional distribution of this antibiotic administration according to the referral base was not statistically significant (χ (2) =6.87, p = 0.3): 70% (14/20) from PHF, 56% (14/25) from SHF, 71% (23/32) from THF, and 63% (23/36) from PC. The antimicrobial agent administered was specified in 40 cases: Ceftriaxone was the commonest antibiotic agent implicated. Conclusion There is apparent unnecessary exposure of patients to antibiotics in the pre-neurosurgical care of neurotrauma in this study. There is, therefore, need for education on antibiotic stewardship to the group of health workers involved.